2021
DOI: 10.3390/ijerph18042114
|View full text |Cite
|
Sign up to set email alerts
|

Serving Children and Adolescents in Need during the COVID-19 Pandemic: Evaluation of Service-Learning Subjects with and without Face-to-Face Interaction

Abstract: The coronavirus disease (COVID-19) outbreak has posed a great challenge to teaching and learning activities in higher education, particularly for service-learning subjects that involve intensive human interaction. Although service-learning may be transformed to a virtual mode in response to the pandemic, little is known about the impact of this new mode on student learning and well-being. This paper reports a university credit-bearing service-learning subject that involves services toward needy children and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
45
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 61 publications
(88 reference statements)
10
45
2
2
Order By: Relevance
“…Generally speaking, data gathered from the objective outcome evaluation tool revealed that university students (i.e., service providers) showed positive changes in cognitivebehavioral competencies, positive identity, positive youth development competencies, service leadership attributes, as well as life satisfaction after taking the SL course in spite of its online/offsite mode of delivery. The present findings are consistent with Lin and Shek's [18] research which found that regardless of the mode of delivery (i.e., face-to-face vs. online), students acquired a wide range of positive youth development outcomes, service leadership qualities, and subjective well-being after completion of an SL course. Furthermore, Guthrie and McCracken [34] conducted a case study of an e-SL course and concluded that "the overall teaching approach serves multiple pedagogical functions focusing on the integration of experience and reflection as the means to further both academic growth and skill development" (p. 250).…”
Section: Objective Outcome Evaluation Of University Studentssupporting
confidence: 91%
See 1 more Smart Citation
“…Generally speaking, data gathered from the objective outcome evaluation tool revealed that university students (i.e., service providers) showed positive changes in cognitivebehavioral competencies, positive identity, positive youth development competencies, service leadership attributes, as well as life satisfaction after taking the SL course in spite of its online/offsite mode of delivery. The present findings are consistent with Lin and Shek's [18] research which found that regardless of the mode of delivery (i.e., face-to-face vs. online), students acquired a wide range of positive youth development outcomes, service leadership qualities, and subjective well-being after completion of an SL course. Furthermore, Guthrie and McCracken [34] conducted a case study of an e-SL course and concluded that "the overall teaching approach serves multiple pedagogical functions focusing on the integration of experience and reflection as the means to further both academic growth and skill development" (p. 250).…”
Section: Objective Outcome Evaluation Of University Studentssupporting
confidence: 91%
“…Specifically, these types of services focus on the advocation of social injustice and promulgate consciousness of certain social issues [17]. However, whether students still gain as much as they would have if SL were conducted in person remains unanswered [18,19].…”
Section: Service-learning At a Distancementioning
confidence: 99%
“…In Hong Kong, a study on the online learning experience under COVID-19 found students faced a decrease in learning effectiveness, studying time and efficiency, and they perceived an increase in studying pressure [29]. However, in the context of service-learning, there is evidence showing that the online service-learning activities under COVID-19 promoted the positive development of both service providers and service recipients [30].…”
Section: Learning Under Covid-19mentioning
confidence: 99%
“…For example, there are studies examining students' perception toward classroom instructed service leadership education and found students were positive to subject content, teachers, and course benefits [22]. Yet, the effectiveness of online service leadership education and students' subjective feelings towards online learning under the circumstance of the pandemic remain unknown [30]. When the instruction becomes more hybrid, it is important to understand course effectiveness and subjective learning experience from students' perspective.…”
Section: Research Gapsmentioning
confidence: 99%
“… 14 , 15 These sites also support the upkeep of online classes because face-to-face classes are not possible in this pandemic. 16 We cannot overlook the importance of ASNS in higher education, as these skills can significantly influence overall academic performance. ASNS, together with other factors such as emotional intelligence, help enhance undergraduate students’ academic performance during the pandemic.…”
Section: Introductionmentioning
confidence: 99%